Korelasi Antara Etika Lingkungan Dan Perilaku Masyarakat Dalam Pelestarian Lingkungan: Tinjauan Literatur - Essy Anesta Asdami; Reflis Reflis; Satria Putra Utama; Yenita Ekasari; Dwi Maryani; Ranti Uchera (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2024)
The correlation between environmental ethics and societal behavior has become an increasingly important subject in the context of environmental conservation. This article presents a literature review of the relationship between individual environmental ethics and community behavior in the context of environmental conservation efforts. Through searching various journals and related publications, we identified key themes, findings and trends in this research. Research shows that environmental ethical values, environmental awareness, and social norms play a key role in shaping individual and collective behavior towards the environment. Factors such as education, personal experiences, and social pressures also influence how individuals and societies respond to environmental issues. Policy implications and suggestions for future research are also discussed.